1987
DOI: 10.4319/lo.1987.32.2.0476
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine incorporation and microbial respiration in the surface sediment of a hypereutrophic lake1

Abstract: This article is in Free Access Publication and may be downloaded using the “Download Full Text PDF” link at right.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 30 publications
0
45
1
Order By: Relevance
“…This test showed that dilution with equal amount of non-radioactive thymidine shut off the de novo pathway. Analyses of benthic heterotrophic bacterial production were then performed according to Bell & Ahlgren (1987), within 1 h after sampling. In short, triplicates were incubated in situ with 0.2 ml sediment and 2.08 µmol l -1 [methyl- ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This test showed that dilution with equal amount of non-radioactive thymidine shut off the de novo pathway. Analyses of benthic heterotrophic bacterial production were then performed according to Bell & Ahlgren (1987), within 1 h after sampling. In short, triplicates were incubated in situ with 0.2 ml sediment and 2.08 µmol l -1 [methyl- ).…”
Section: Methodsmentioning
confidence: 99%
“…The incubations were stopped with 5 ml of 80% ethanol and the samples were transported to the laboratory where they were kept at 4°C until further analysis. DNA was extracted and the samples were measured in the scintillation counter according to Bell & Ahlgren (1987). The empirical conversion factor of 2 × 10 18 cells mol -1 incorporated thymidine was used to calculated the production of heterotrophic bacteria (Bell 1993).…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, these data suggest that total heterotrophic bacterial activity should not be measured with the [)H]TdR uptake method in environments where SRB are important contributors to total microbial growth, including most estuarine and shallow-water marine sediments (other than surficial sediment floes: Fallon et al 1983;Bell and Ahlgren 1987), anoxic saline waters, and sediments of freshwaters in which SOb2-levels are raised. Use of thymidine uptake in these systems may grossly underestimate bacterial production, depending on the relative amount of S0,2--reducing activity in the sample.…”
mentioning
confidence: 94%
“…Thus, any potential overestimation of DNA synthesis (at most by 25 %) is counteracted by the corresponding loss of DNA (20 to 30 % ) during the extraction procedures (Findlay et al 1984, Bell & Ahlgren 1987, Wicks & Robarts 1987. We measured adenine incorporation into protein (hot-TCA-insoluble material) during stationary phase and found that incorporation into pro-tein was 20 to 30 % of total incorporation into DNA + protein.…”
Section: Methodsmentioning
confidence: 99%